(untitled) (Research, Society and Development, 2020)
Objective: To identify the experience of depressive symptoms by undergraduate nursing students in the midwest of the state of São Paulo. Method: An exploratory, descriptive study with a quantitative approach, carried out with 94 undergraduate nursing students. Data were collected in 2018, using a semi-structured questionnaire and applying the Beck Depression Inventory, and analyzed using descriptive statistical analysis. Results: Of the 94 (100%) participants, 82 (87.2%) were female, 46 (47.9%) aged 17 to 21 years, 86 (89.6%) heterosexual, 74 (77, White skin color), 27 (28.1%) with family income between 1 and 2 minimum wages. Regarding depressive symptoms, 81 (86.2%) said they did not have a previous diagnosis for depression, of which nine (11.1%) had dysphoria and five (6.2%) had depression. Participants who claimed to have a previous diagnosis of depression were 13 (13.8%) of the total participants, of whom, seven (53.8%) had mild depression, three (23.1%) with moderate depression and one (7 , 7%) with severe depression. Important data that are related to depressive symptoms and family life are also reported. Conclusion: The presence of depressive symptoms directly affects the performance of some students, especially those who are preparing to enter the job market. Actions are proposed, within the institution, so that professionals with better mental health are trained, in addition to direct support to students so that there is no worsening of the situation or any impairment in learning.